A METHODOLOGICAL FRAMEWORK FOR IDENTIFYING EMPLOYMENT GROWTH DRIVERS IN THE ARCTIC ECONOMY - Vladimir Nikolaevich Myakshin (Север и рынок: формирование экономического порядка)
Developing an effective employment system in the Arctic regions in the context of stagnant demographic and migration trends requires identifying types of economic activities that significantly influence employment growth. This necessity underscores the relevance of the research. The study aims to determine sectoral priorities for boosting employment by identifying key employment growth drivers. The research hypothesis posits that sectors of economic specialization with a positive regional component in structural changes (indicating favorable regional factors) should be classified as employment growth drivers. To analyze the sectoral employment structures of the Arctic regions, the shift-share analysis method was employed, enabling the evaluation of the impact of national, sectoral, and regional factors on regional employment. This was complemented by the calculation of localization coefficients to assess the competitiveness and growth potential of economic activities from an employment perspective. The study’s primary contribution lies in developing an algorithm for identifying key employment growth drivers through structural change analysis and specialization analysis. The research introduces a novel classification system for economic activities based on localization coefficients and regional structural shifts. This classification distinguishes three groups: key employment growth drivers, potential employment growth drivers, and possible future employment growth drivers. The proposed methodology was tested using official data from the Federal State Statistics Service for the Arctic regions. The study assessed the employment growth potential of various economic activities and classified them according to the defined criteria. Identifying key employment growth drivers contributes to the scientific foundation of regional employment policies, a critical component of socio-economic development in the Arctic economy. This emphasizes the study’s relevance and its scientific and practical significance. Future research should focus on developing models that account for interrelations between economic activities and their multiplier effects.